Storytellers - an account of the creation of spaces from the encounters with the Tikuna in the Parque das Tribos (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article proposes to reflect on the research carried out in the field of pedagogical practices and poetic experiences lived with the indigenous people of the Tikuna ethnic group. These sensitive meetings were guided by the search for dialogue with Amerindian knowledge and the creation of a space of knowledge and cultural exchanges that potentiates the voices of the subjects involved - the indigenous people, the student-performers and the performer-teacher. Meetings with other bodies, people, groups, experiences, places, ideas, stories, cultures, ethnicities and gender, constituting the network of collaborations. These meetings speak about the experience with the indigenous community Parque das Tribos located in the urban perimeter of the city of Manaus, Amazonas, where the focus is on the exchange relationship with teacher Tikuna Mepaeruna and the Tikuna children at the Uka Umbuesara Wakenai Anumarehit Cultural Space, assisted by the Indigenous School Education Management (GEEI / SEMED) established within the community.
Keywords: Meetings; Storytelling; Artistic-pedagogical practice; Amerindian knowledge